Comparative evaluation of Ambu Aura-i and Fastrach™ intubating laryngeal mask airway for tracheal intubation: A randomized controlled trial - Lakesh Anand; Manpreet Singh; Dheeraj Kapoor; Anjali Singh (Wolters Kluwer Medknow Publications, 2019)
Background and aims: Ambu Aura-i was compared with Fastrach™ (FT)-laryngeal mask airway (LMA) as a conduit for tracheal intubation. Material and Methods: A hundred consenting patients were randomly allocated into two groups of 50 patients each in a prospective randomized study. Standard anesthesia technique was used for all patients and FT-LMA or Ambu Aura-i was selected. After insertion of airway device, the cuff was inflated and ventilation was attempted. Once satisfactory ventilation was achieved, with or without maneuvers, a fiberoptic scoring for glottis view was noted. A polyvinylchloride (PVC) tracheal tube of appropriate size was inserted through the airway device as per procedure. If no resistance was felt while advancing the tracheal tube, it was fully inserted into the device and tracheal tube cuff was inflated. The device was removed and tracheal tube was left in situ. If the first attempt failed during tracheal tube insertion, the recommended maneuvers were used. A maximum of three attempts were allowed for intubation. First attempt for tracheal intubation attempt was a blind, second attempt was made with maneuver. If second attempt of intubation was unsuccessful, fiberoptic-guided intubation was performed as a third attempt. When tracheal intubation was unsuccessful, it was performed by direct laryngoscopy and considered as failed intubation. Rest of the anesthesia management was as per the discretion of attending anesthesiologists. The success rate of device insertion, fiberoptic score of glottis view, tracheal intubation via FT-LMA or Aura-i and time were recorded. Results: Both FT-LMA and Aura-i were successfully placed within two attempts. The success rate of blind intubation was 92% in FT-LMA and 76% in Aura-i (P < 0.01). Time taken for tracheal intubation at first attempt was lesser in group FT-LMA and Aura-i, respectively (P < 0.01). Fiberoptic-guided intubation success rate was higher with Aura-i than with FT-LMA. Conclusions: FT-LMA had a higher success rate in facilitating blind tracheal intubation compared with Ambu Aura-i.